Assessment of productivity and resource use efficiency of rice under different establishment methods and nutrient management in Chitwan condition, Nepal - Lama, Chandika; Marahatta, Santosh (Journal of Agriculture and Environment, 2018)
A field experiment was conducted in sub humid climate of inner terai of Nepal to determine the productivity and economics of rice under direct seeded and transplanted methods under different nutrient management in strip plot design with three replications in 2013, rainy season. The treatment consisted of three tillage methods, conventional tillage direct seeded rice, unpuddled transplanted rice and Puddled transplanted rice and five nutrient management practices Recommended Nitrogen(N), Phosphorous(P) and Potassium(K), 100:30:30 Kg NPK ha-1; Leaf color chart based N + Recommended PK; Farmers’ Practice, 48.30:34.50:0.00 Kg NPK ha-1; 0N + Recommended PK and 150% of Recommended NPK. The result revealed that grain and straw yield were not significant due to crop establishment methods. LCC based N application yield was comparable with 150% of Rec. NPK and Rec. NPK. Saving N on LCC based N management with 41.56 Kg ha-1 and 9.44 Kg N ha-1 over 150% of recommended NPK recommended NPK respectively. Adoption of CT-DSR reduced the total cost of cultivation by 30.13% and B:C ratio by 45.95% over P-TPR. The lower cost, higher benefit and the same production, revealed that LCC based N management under CT-DSR was the best management practices over the conventional P-TPR.